1997
DOI: 10.1038/sj.gt.3300453
|View full text |Cite
|
Sign up to set email alerts
|

Selection and use of ligands for receptor-mediated gene delivery to myogenic cells

Abstract: Identification of myogenic cell targeting ligands is a critical observed in regenerating fibers of patients with Duchenne step in the development of synthetic vectors for gene delivmuscular dystrophy and the ability to direct a large enzyme ery to skeletal muscle. Here we describe the screening of conjugate to the cytoplasm of myotubes. Finally, we show six potential targeting ligands (insulin, insulin-like growth that incorporation of transferrin into an artificial virus confactor I, iron transferrin, gallium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
(12 reference statements)
1
17
0
Order By: Relevance
“…This is the first study reporting a liposome formulation that is completely unaffected by the presence of 95% serum. With this system we have been able to achieve a transfection efficiency in primary myoblasts comparable to that obtained by Feero and colleagues 19 in a serumfree environment using muscle-targeted liposomes. We therefore believe that the DODAC system holds considerable potential as a basis for further development, especially in the direction of improving the transfer of plasmid DNA from the cytoplasm to the nucleus.…”
Section: Figure 5 Luciferase Activity Following Transfection With Lipsupporting
confidence: 62%
See 1 more Smart Citation
“…This is the first study reporting a liposome formulation that is completely unaffected by the presence of 95% serum. With this system we have been able to achieve a transfection efficiency in primary myoblasts comparable to that obtained by Feero and colleagues 19 in a serumfree environment using muscle-targeted liposomes. We therefore believe that the DODAC system holds considerable potential as a basis for further development, especially in the direction of improving the transfer of plasmid DNA from the cytoplasm to the nucleus.…”
Section: Figure 5 Luciferase Activity Following Transfection With Lipsupporting
confidence: 62%
“…The few reports that have dealt with the use of cationic liposomes to transfect cultured muscle cells obtained significant transfection levels only in a serumfree environment. 9,13,18,19 We and others have shown that the efficiency of liposome-DNA complexes (lipoplexes) is drastically inhibited by the presence of serum 9,11,13 and that DNA precondensation with polylysine (lipopoliplexes) can partially correct this inhibition. 9 However, the experiments reported so far were carried out at most in the presence of 10% serum, a condition that is far from that present in vivo, and the transfection levels were extremely low.…”
Section: Discussionmentioning
confidence: 99%
“…13 We and others have explored different strategies for muscle-specific targeting in adult mouse muscle. [14][15][16][17][18] However, vector retargeting to enhance fetal gene transfer of muscle or other tissues has not been reported previously for any viral or nonviral vectors. Incorporation of an Arg-GlyAsp (RGD) peptide motif, which binds to vitronectin integrins, in the fiber knob of Ad vectors increases transduction efficiency of cells in culture.…”
Section: Introductionmentioning
confidence: 99%
“…16 It is also postulated that phenotypic correction of DMD requires restoration of about 20% of normal dystrophin levels in affected dystrophic muscles. 15,17 This level of dystrophin gene expression in limb muscles has recently been achieved in mdx mice transduced with a new type of adenoviral vector 4 and this approach looks especially promising when supplemented with transient immunosuppression. 5 Retroviral transduction or nonviral dystrophin gene delivery resulted in much less conspicuous transgene expression.…”
Section: Discussionmentioning
confidence: 99%